Chapter 2 Investigating waiting Interdisciplinary thoughts on researching elongated temporalities in healthcare settings - Anucha, Kelechi (Taylor & Francis, 2021)
Researching 'waiting' necessitates practices of attunement to multiple coexisting temporalities and careful processes for handling and holding the temporal material produced by these practices. In this chapter, we share some of what has been learned from experiments in 'making time' as a research practice, in which we have had to invent the relations needed to give the temporal a thinkable form. We bring together accounts from three collaborative projects about waiting in health settings, where waiting is fundamentally linked to practices of care. Each project sits within its own discipline (publicly-engaged literary studies, artistic practice-as-research, and psychosocial studies), leading researchers to experiment with different forms and concepts through which time as an 'object' might be attended to, grasped and indeed 'made' in the process.